Neuroscience, brains, and computers - Innocenti, Giorno Maria (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This paper addresses the role of the neurosciences in establishing what the brain is and how states of the brain relate to states of the mind. The brain is viewed as a computational deviceperforming operations on symbols. However, the brain is a special purpose computational devicedesigned by evolution and development for survival and reproduction, in close interaction with theenvironment. The hardware of the brain (its structure) is very different from that of man-made computers.The computational style of the brain is also very different from traditional computers: the computationalalgorithms, instead of being sets of external instructions, are embedded in brain structure. Concerningthe relationships between brain and mind a number of questions lie ahead. One of them is why andhow, only the human brain grasped the notion of God, probably only at the evolutionary stage attainedby Homo sapiens.